Exploring the institutional sustainability of adolescent reproductive and sexual health program in Tripura - Baidya, Subrata; Reang, Taranga; Chowdhury, Purvita; Paul, Debosmita (International Journal Of Community Medicine And Public Health, 2019)
Background: Adolescents are at the peak of growth velocity and warrant special consideration as they undergo enormous psychological, physical as well as cognitive changes. The Government of India implemented friendly adolescent reproductive and sexual health (ARSH) clinics to improve healthcare services all over the country. However, there is lack of information on the sustainability of the programme. Methods: Community workers and public health workers from randomly selected twenty sub centres for intervention from West Tripura district and control from the adjacent Khowai district were selected. Knowledge prior and post intervention at both sites of the health workers was assessed by a self-administered questionnaire on 0 day, at 3, 6 and 12 months. Difference of knowledge score was analysed by paired t-test. Results: The mean knowledge score significantly differed at pre-intervention and immediately post intervention (p<0.01). The knowledge score was sustained even after 12 months of intervention among public (14.63±3.01) and community health workers (12.53±2.91). However, at the control site, a gradual decrease was noted over duration of 12 months. Intervention also considerably increased the utilization of ARSH clinics by both male and females in comparison to previous year’s data. Conclusions: The intervention and increased sustainability of acquired knowledge over 12 months seem to enhance the capacity for the adolescent clinics. Therefore, training the health workers to manage various sexual and reproductive health issues along with creating a friendly environment for adolescents is indispensable in the present setting.